A nomenclatorial confusion in Tanymastigidae (Crustacea: Branchiopoda: Anostraca) - Cohen, Rosa Graciela (Zootaxa, 2013)
Brtek (1972) established the subfamily Tanymastiginae into Branchipodidae for the genus Tanymastix Simon, 1886 and his new genus Tanymastigites. Although the author did not explicitly designate a type genus, he created the subfamily name on the stem of the older genus that he included in his new subfamily. The name Tanymastix (in genitive singular, Tanymastigis: stem Tanymastig- and desinence -is) gives the subfamily name Tanymastiginae Brtek, 1972.